Overproduction of Escherichia coli integration host factor, a protein with nonidentical subunits. - Nash, H A (1987)
Integration host factor (IHF) is a small, basic protein that is needed for efficient recombination of bacteriophage lambda, as well as for other host and viral functions. We have constructed strains in which the two subunits of IHF, encoded by the himA and hip genes of Escherichia coli, are expressed under the control of the lambda rho L promoter. Separate overexpression of himA and hip led to the production of unstable and insoluble peptides, respectively. In contrast, the overexpression of both genes conjointly led to the accumulation of large amounts of active IHF. Extracts of such cells provided the starting material for a rapid purification procedure that results in milligram quantities of apparently homogeneous IHF.